Modeling Life - Garfinkel, Alan; Shevtsov, Jane; Guo, Yina (Springer, 2017)
This course was designed to supplant the traditional “Calculus for Life Sciences” course generally required for freshman and sophomore life science students. The standard course is limited to calculus in one variable and possibly some simple linear differential equations. It stresses the technical development of the subject. There is an emerging consensus that a more relevant course would feature ✔ A significant use of real examples from, and applications to, biology. These examples should come from physiology, neuroscience, ecology, evolution, psychology, and the social sciences. ✔ Much greater emphasis on concepts, and less on technical tricks. ✔ Learning the rudiments of a programming language sufficient to graph functions, plot data, and simulate differential equations. This view has been taken by all the leading voices in US biomedical research. For example, the Howard Hughes Medical Institute (HHMI) and the Association of American Medical Colleges, in their 2009 publication “Scientific Foundations for Future Physicians,” identified key “Undergraduate Competencies,” which include the ability to – “Quantify and interpret changes in dynamical systems.” – “Explain homeostasis in terms of positive or negative feedback.” – “Explain how feedback mechanisms lead to damped oscillations in glucose levels.” – “Use the principles of feedback control to explain how specific homeostatic and reproductive systems maintain the internal environment and identify · how perturbations in these systems may result in disease and · how homeostasis may be changed by disease.”
The Mathematics of Biological Systems